Perocidase Isoenzymes in Rye and Diploid, Tetraploid and Hexaploid Wheats - Bhandal, Manjit S (Annals of Arid Zone, 2016)
Isoenzymes of peroxidase were studied in mots of 72-hour-old seedlings of rye and two diploid, five tetraploid and three heraploid species of wheat employing horizontal starch gel electrophoresis. Them werc interspecific differences and some of these could he correlated a i l h specific genome and/or ploidy level.